2015
DOI: 10.18357/ijcyfs.63201513562
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic and Gender Sensitive Understanding of Adolescents’ Personal and School Resilience Characteristics Despite Family Violence: The Predictive Power of the Family Violence Burden Level

Abstract: Abstract:In this cross-sectional study on family violence and resilience in a sample of 5,149 middle-school students with a mean age of 14.5 years from four European Union countries (Austria, Germany, Slovenia, and Spain), we worked from the premise that resilience should not be conceptualized as a dichotomous variable. We therefore examined the gender-specific personal and social characteristics of resilience at the three levels "resilient", "near-resilient", and "non-resilient". We also expanded our definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Identifying violence-resilience outcomes and recognizing adolescents' resilience after they experience parental physical abuse is a complex endeavor. Even though adolescents experiencing parental abuse commonly show psychopathological symptoms, international research confirms that about one-third of adolescents physically abused by parents do not show psychopathological symptoms, such as depression and aggression toward peers [7,41].…”
Section: Conceptualizing Violence-resilience Outcomes Of Adolescents ...mentioning
confidence: 99%
“…Identifying violence-resilience outcomes and recognizing adolescents' resilience after they experience parental physical abuse is a complex endeavor. Even though adolescents experiencing parental abuse commonly show psychopathological symptoms, international research confirms that about one-third of adolescents physically abused by parents do not show psychopathological symptoms, such as depression and aggression toward peers [7,41].…”
Section: Conceptualizing Violence-resilience Outcomes Of Adolescents ...mentioning
confidence: 99%
“…Different criteria, in turn, lead to different outcomes, more complicating the comparison of these outcomes, and do not provide space for youths who cannot or should not be clearly labeled as resilient or non-resilient. As one of the less common examples, Kassis et al (2013b , 2015) operationalized violence resilience non-dichotomously and showed that youths can find their place between the extremes of resilient and non-resilient and that the absolute achievement of resilience is not necessarily the only positive form of development, but a continuum-based resilience can be a useful alternative to the dichotomous operationalization. In a cross-sectional study of family violence and resilience in a random sample of 5,149 middle school students in Europe, the researchers found that 31% of youths were resilient, 28.3% near-resilient (mid-level scores for violence perpetration and/or depression symptoms), and 40.6% non-resilient ( Kassis et al, 2013b ).…”
Section: Violence Resilience As a Risk-specific Theoretical Frameworkmentioning
confidence: 99%
“…Presently, the fourth wave is said to be in ascendance, as the discoveries of the first three waves become assimilated with more sophisticated methods of investigation to develop a richer understanding of the multilevel, contextualized, and dynamic nature of resilience (e.g., Kassis, Artz, Moldenhauer, Geczey, & Rossiter, 2015). Using Bronfenbrenner's (1977) human ecology theory, an ecological understanding of resilience places both the individual and the adversity within a dynamic multilevel context, where the impact of higher level factors (e.g., social, economic, cultural) on factors proximal to children is emphasized (Cassen, Feinstein, & Graham, 2009).…”
Section: Research-article2016mentioning
confidence: 99%